2018
DOI: 10.1161/strokeaha.117.020544
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Role of Neutrophils Through Function of Lactoferrin After Intracerebral Hemorrhage

Abstract: LTF delivered to the ICH-affected brain by infiltrating PMNs may assist in hematoma detoxification and represent a powerful potential target for the treatment of ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 48 publications
2
60
0
Order By: Relevance
“…Hematoma following ICH can directly compress brain tissue, which further induces mechanical damage and secondary brain injury [19,20,21]. In ammation contributes to brain damage following ICH, leading to macrophage activation and blood-brain barrier (BBB) disruption [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma following ICH can directly compress brain tissue, which further induces mechanical damage and secondary brain injury [19,20,21]. In ammation contributes to brain damage following ICH, leading to macrophage activation and blood-brain barrier (BBB) disruption [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…7,25,26 However, inflammation has also been associated with brain recovery in the ICH setting. 7,27 Therefore, the role of inflammation in brain injury and recovery after ICH has not been completely defined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results may provide another evidence for future statin use in ICH patients, and more related researches were needed to understand the potential mechanism. Interestingly, a recent work reported that systemic depletion of PMNs at 24 h after ICH exacerbated neurological deficits, suggesting that PMNs infiltration into the brain also shows some beneficial function at the subacute stage post-ICH (Zhao et al, 2018). After further investigation, they proposed that PMNs-mediated protective effect in subacute stage may through the two following ways: (1) PMNs can deliver cytoprotective lactoferrin to the ICH-affected brain, neutralizing iron and blocking its toxicity (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent work reported that systemic depletion of PMNs at 24 h after ICH exacerbated neurological deficits, suggesting that PMNs infiltration into the brain also shows some beneficial function at the subacute stage post-ICH (Zhao et al, 2018). After further investigation, they proposed that PMNs-mediated protective effect in subacute stage may through the two following ways: (1) PMNs can deliver cytoprotective lactoferrin to the ICH-affected brain, neutralizing iron and blocking its toxicity (Zhao et al, 2018). (2) ICH can also transform the phenotype of PMNs that entering brain at the later stages, which then could enhance the beneficial effects like promoted blood detoxification efficacy (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%